Decline effects are rare in ecology. Issue 6 (13th April 2022) - Costello, Laura; Fox, Jeremy W.
Abstract: The scientific evidence base on any given topic changes over time as more studies are published. Currently, there is widespread concern about nonrandom, directional changes over time in the scientific evidence base associated with many topics. In particular, if studies finding large effects (e.g., large differences between treatment and control means) tend to get published quickly, while small effects tend to get published slowly, the net result will be a decrease over time in the estimated magnitude of the mean effect size, known as a "decline effect." If decline effects are common, then the published scientific literature will provide a biased and misleading guide to management decisions, and to the allocation of future research effort. We compiled data from 466 meta‐analyses in ecology to look for evidence of decline effects. We found that decline effects are rare. Only 5% of ecological meta‐analyses truly exhibit a directional change in mean effect size over time arising for some reason other than random chance, usually but not always in the direction of decline. Most apparent directional changes in mean effect size over time are attributable to regression to the mean, consistent with primary studies being published in random order with respect to the effect sizes they report. Our results are good news: decline effects are the exception to the rule in ecology. Identifying and rectifying rare cases of true decline effects remains an important task, but ecologists should not overgeneralize from anecdotal reports of decline effects.